Noun phrases and nominalization in Basque : syntax and semantics - Etxeberria, Urtzi; Etxepare, Ricardo; Uribe-Etxebarria, Myriam (Linguistik aktuell, 2012)
This collective volume on nominal expressions in Basque, a language isolate with no known relatives, comprises original papers on the syntactic structure and the interpretation of both noun phrases and nominalization constructions - a traditionally neglected aspect of Basque linguistics. The minute attention to properties and paradigms previously overlooked, and the analyses of them in the light of recent advances in syntactic theory make this book a valuable tool for syntacticians, semanticists and morphologists. This work fills a gap in the theoretical study of Basque.